b(a-4)=c

Simple and best practice solution for b(a-4)=c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b(a-4)=c equation:


Simplifying
b(a + -4) = c

Reorder the terms:
b(-4 + a) = c
(-4 * b + a * b) = c

Reorder the terms:
(ab + -4b) = c
(ab + -4b) = c

Solving
ab + -4b = c

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '4b' to each side of the equation.
ab + -4b + 4b = 4b + c

Combine like terms: -4b + 4b = 0
ab + 0 = 4b + c
ab = 4b + c

Divide each side by 'b'.
a = 4 + b-1c

Simplifying
a = 4 + b-1c

See similar equations:

| 8+b+5-3b=-3-4b | | (x+3)/4=(x+5)/6 | | 5x^2-18x-6=0 | | x*x=(8.75*8.75)+(x-1)*(x-1) | | 35n-81=234 | | 4/5x7/8 | | -12=-3 | | x/(x+11)(x-11) | | 3x=5-8 | | (Y+2)=g | | 8b+1-b=8+7b+4 | | x*x=(8.67*8.67)+(x-1)*(x-1) | | z^2+i=0 | | 2d(d-2)=-7 | | x^2-3x-108= | | 38-(2c+4)=4(c+5)c | | 3x=-5x-8 | | 9x-2(3x+1)=x+1 | | -3=-9x-3 | | .09x^2-2.007x+.00012=0 | | 4(x-2)=3(x-2) | | 1/4(x-8)+7 | | x-32=-27 | | 2x-4y=12fory | | 2r+-6r=12 | | Ym+3=n | | -3m+4m-2=m-2 | | 5m+7.75=40.25 | | 5(h-1)=2(h-4)-6 | | 7/8*16 | | -6w+4=-2(3w-2) | | x/9+x=5/8 |

Equations solver categories